(untitled) (Journal of Atomic and Molecular Sciences, 2014)
By employing the linear combination operator and the unitary transformation methods, we study the vibrational frequency and the ground state energy of a strong-coupling polaron in symmetric RbCl quantum dots (SRQDs). The effects of the temperature and the confinement strength are taken into account. It is found that the vibrational frequency and the ground state energy are increasing functions of the temperature and the confinement strength. We find two ways of tuning the vibrational frequency and the ground state energy via adjusting the temperature and the confinement strength.